Model and Strategies for Sports Tourism Management of The Western Region in The Context of Thailand 4.0 - Meenoi, Prapatsorn; Sungrugsa, Narin (Dusit Thani College Journal, 2020)
The purposes of this research were to : 1) study situation and need of sports tourism management in the western region in the context of Thailand 4.0, 2) synthesize sports tourism management model of the western region in the context of Thailand 4.0, 3) analyze and define sports tourism management strategies for the western region in the context of Thailand 4.0, and 4) affirm sports tourism management model and strategies of the western region in the context of Thailand 4.0. The methodologies of this research were mixed between policy research and Ethnographic Delphi Futures Research. The data were collected by document analysis, participatory observation, and in-depth of interview thirty professionals and stakeholders. The assessment of the appropriateness of the strategies were done by seventeen experts. The results of the study are as follows: 1) For about the tourism situation and needs, the study found that the western region has the potential of tourism resources and is ready to develop sports tourism management. In addition the government should set a clear policy on sports tourism for each area while creating a new model of sports tourism to meet the tourists' needs. 2) Sports tourism management model of the western region in the context of Thailand 4.0 is “SPORT- K Model”: S – Standard, P – Participation, O – Organizing, R – Responsibility T - Technology and Innovation and K – Knowledge. 3) From the analysis of this study the researcher anticipated five sports tourism management strategies which include: (1) potential development of sports tourism management in the western region, (2) promotion of the price and value added by using local resources to create sports tourism activities, products and services on the basis of community identity through the participation of communities, networks and stakeholders, (3) development of sports tourism management to balance community tourists and stakeholders, (4) development mechanism to drive sports tourism management in the western region, and (5) development of human resources through technology and innovation to strengthen sports tourism activities that support Thailand 4.0. 4) The Policy Meeting found that stakeholders had a consensus that the model and five strategies of sports tourism in the western region in the context of Thailand 4.0 were appropriate and feasible.